2018
DOI: 10.1111/mpp.12653
|View full text |Cite
|
Sign up to set email alerts
|

Peptidoglycan hydrolysis mediated by the amidase AmiC and its LytM activator NlpD is critical for cell separation and virulence in the phytopathogen Xanthomonas campestris

Abstract: SUMMARYThe essential stages of bacterial cell separation are described as the synthesis and hydrolysis of septal peptidoglycan (PG). The amidase, AmiC, which cleaves the peptide side-chains linked to the glycan strands, contributes critically to this process and has been studied extensively in model strains of Escherichia coli. However, insights into the contribution of this protein to other processes in the bacterial cell have been limited. Xanthomonas campestris pv. campestris (Xcc) is a phytopathogen that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 51 publications
3
30
0
Order By: Relevance
“…Meanwhile, in the genus Burkholderia, it has been shown that the inactivation of the periplasmic AmiC amidase causes the loss of daughter cell separation capacity, obviously entailing a severe impairment for motility, which was translated into the impossibility of causing infection in the rat model or colonizing the insect gut (68,69). Similar results for AmiC of the phytopathogen Xanthomonas campestris have been reported, together with negative effects on type III secretion system (T3SS) performance, obviously entailing an impairment of virulence (70). Nevertheless, at present it remains to be seen whether this impairment of the T3SS function could be related to defects in the insertion of its machinery through the PGN layer (caused by the AmiC absence), as will be displayed later for other proteins.…”
Section: Periplasmic Actors Other Than Penicillin Binding Proteinsmentioning
confidence: 64%
“…Meanwhile, in the genus Burkholderia, it has been shown that the inactivation of the periplasmic AmiC amidase causes the loss of daughter cell separation capacity, obviously entailing a severe impairment for motility, which was translated into the impossibility of causing infection in the rat model or colonizing the insect gut (68,69). Similar results for AmiC of the phytopathogen Xanthomonas campestris have been reported, together with negative effects on type III secretion system (T3SS) performance, obviously entailing an impairment of virulence (70). Nevertheless, at present it remains to be seen whether this impairment of the T3SS function could be related to defects in the insertion of its machinery through the PGN layer (caused by the AmiC absence), as will be displayed later for other proteins.…”
Section: Periplasmic Actors Other Than Penicillin Binding Proteinsmentioning
confidence: 64%
“…Accordingly, the next pair of mutations occur in an unrelated locus: nlpD ( pflu1301 ), which encodes a lipoprotein predicted to have a function in cell wall formation and cell separation in a range of bacteria (Stohl et al 2016; Lind et al 2017; Tsang et al. 2017; Yang et al. 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have mostly considered that nlpD is related to envelop integrity and iron acquisition [ 44–46 ]. However, a few studies reported that nlpD affects virulence in the phytopathogens Xanthomonas [ 47 ] and Yersinia pestis [ 48 ]. Except in Yersinia pestis , however, the virulence mechanism of nlpD remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%